Microbial Community and Its Association With Physicochemical Factors During Compost Bedding for Dairy Cows - Sun, Likun; Han, Xiangmin; Li, Jianshu; Zhao, Zhidong; Liu, Yuzhen; Xi, Qiming; Guo, Xinyu; Gun, Shuangbao (Frontiers in Microbiology, 2020)
Overproduction of livestock manure can cause significant environmental challenges. Compost bedding (CB) is considered an effective approach for recycling the agricultural byproducts and improving the welfare of dairy cattle. In the process of preparing compost bedding, the composition of microbial communities gets altered; however, our knowledge of the patterns and drivers of CB microbial communities remains limited. The current study aimed to explore the dynamics of bacterial and fungal communities during the various padded stages, using high throughput sequencing technology. The relationships across physicochemical parameters, microbial community composition, and abundance were also evaluated. Sequencing results revealed Proteobacteria, Bacteroidetes, Actinobacteria, and Firmicutes of bacteria, and Ascomycota of fungi as the major phyla. Linear discriminant analysis effect size (LEfSe) showed Actinobacteria as the indicator in raw materials and Bacteroidetes in the other padded stages. Dothideomycetes was significantly enriched in the initial stage of fungi, whereas Sordariomycetes, including a pathogen Scedosporium prolificans, was the major indicator group in CB after nine days of padding. Mantel test showed that pH could significantly influence bacterial community composition while temperature and total organic carbon had a significant effect on fungal community structure. Redundancy analysis (RDA) indicated that total organic carbon (TOC), temperature, and water content had a significant effect on bacterial abundance while total nitrogen (TN), water content, and pH significantly affected fungal abundance. Our finding increases the understanding of microbial community succession in compost bedding across different padded stages, and suggests CB management by changing the bedding material every seven days.